Obtenção de chips de berinjela (Solanun melongena L.) mediante processo combinado de desidratação osmótica em solução ternária e secagem convectiva - Fernandes, Maristela Alves (2012)
This work aimed to utilize the combined osmotic dehydration and convective drying process to obtain eggplant chips by a non-conventional healthier and more low cost way. The combined process was studied through a factorial experimental design having as independent variables the temperature (30-50°C), sucrose (27,5 to 42,5% w/w) and sodium chloride (3,75 to 6,25% w/w) solution concentrations and immersion time (142,5 to 247,5 min.). The dependent ones were the water loss (PA), sucrose gain (GSac), sodium gain (GSódio), and the GSac/GSódio ratio. Samples from each osmotic condition were dried at 60°C for 4 hours in a convective dryer with a 1m/s air velocity. The objective was to obtain a maximum water loss with a minimum sucrose and sodium impregnation. Statistic models were well fitted according to the Response Surface Methodology. Once PA was above 90% and water activity was less than 0,4 for all samples, it was used the GSac/GSódio ratio as a parameter for choosing the best process condition which should be maximum. Thus, from this analysis, the best way to obtain eggplant chips was at 50°C, with a sucrose and sodium chloride concentrations of 45% and 7,5%, respectively, for 127,5 minutes. This independent variables combination led to a final product with its sodium content sensory attenuated due the sucrose presence and based on this point of view, it could be considered a healthier product compared with similar commercial, as well as by non-use of conventional frying process.